PENGARUH KONSUMSI ASAM LEMAK (OMEGA-3) TERHADAP DISMENORE - Mochamad Fajar Permana; Wahyu Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Dysmenorrhea is a pain in women when menstruating, it starts when they first experience menstruation and then it will increase in general aged 15-17 years and reach a peak in general aged 20-24 years after that will continue to decline. This is very disturbing daily activities even for many teenage women do not go to school when experiencing menstrual pain, the cause is due to uterine muscle contractions. The uterine muscle contraction is triggered by the hormone prostaglandin, which levels will increase before menstruation begins. This is what causes the appearance of pain and cramps before or during menstruation. The author of the article aims to determine the effect of consumption of fatty acids (omega-3s) on dysmenorrhea.